Design of multifunction bench and picnic table/ Muhammad Khalaf Zakaria - Zakaria, Muhammad Khalaf (2014)
Furniture is a necessity that is now becoming a trend from time to time in accordance with current technological development. In the furniture development, an increasingly trend for the more compact of the space saving furniture are made in demand. Therefore, to address this problem, furniture designs with various functions that can be used in limited space such as the small room, apartment, parks, and picnic areas. Multifunctional furniture such as benches and picnic tables are able to achieve a high demand in the world market based on demand from consumers and the problems they faced. These statements are made based on the results of the questionnaire for the user based on the type of wood used, the concept of function, durability and comfort, saving space, and the market price for the unit. Results have shown that majority of the consumers support or accept multifunction products such as benches and picnic tables as an alternative that can solve the problem of space saving and cost- saving rate of production and marketing costs. In addition, based on the results of most users agree or prefer to use multi-functional furniture as part of their household items.